A mass spectrometry imaging approach on spatiotemporal distribution of multiple alkaloids in Gelsemium elegans - Wu, Zi-Han; Wang, Ruo-Zhong; Sun, Zhi-Liang; Su, Yi; Xiao, Lang-Tao (Frontiers in Plant Science, 2022)
Gelsemium elegans contains multiple alkaloids with pharmacological effects, thus researchers focus on the identification and application of alkaloids extracted from G. elegans. Regretfully, the spatiotemporal distribution of alkaloids in G. elegans is still unclear. In this study, the desorption electrospray ionization mass spectrometry imaging (DESI-MSI) was applied to simultaneously analyze the distribution of pharmacologically important alkaloids in different organ/tissue sections of G. elegans at different growth stages. Finally, 23 alkaloids were visualized in roots, stems and leaves at seedling stage and 19 alkaloids were observed at mature stage. In mature G. elegans, 16 alkaloids were distributed in vascular bundle region of mature roots, 15 alkaloids were mainly located in the pith region of mature stems and 2 alkaloids were enriched in epidermis region of mature stems. A total of 16 alkaloids were detected in leaf veins of mature leaves and 17 alkaloids were detected in shoots. Interestingly, diffusion and transfer of multiple alkaloids in tissues have been observed along with the development and maturation. This study comprehensively characterized the spatial metabolomics of G. elegans alkaloids, and the spatiotemporal distribution of alkaloid synthesis. In addition, the results also have reference value for the development and application of Gelsemium elegans and other medicinal plants.